Comparative Analysis of the Usage of Concept "Hospitality" in Materials of English, Russian and Uzbek Languages - Diyora, Sharofova (European Journal of Life Safety and Stability (2660-9630), 2021)
The refereed scientific research is devoted to the study of the methods of linguistic conceptualization of one of the most important social factors of human life - the sphere of hospitality. The concept of hospitality, using the terminology of A. Vezhbitskaya, is nationally specific for both Russian, English and Uzbek linguistic consciousness and is one of the basic concepts of culture. In the context of the anthropocentric paradigm of linguistics, the work examines the problem of actualizing the "phraseological picture of the world" (FKM) through the phraseology of different languages, a broad interpretation of which includes proverbs and sayings.